"God Smites You!": Atheists' Experiences of Stigma, Identity Politics, and Queerness*. Issue 4 (3rd April 2019) - Loren, Degan; Rambo, Carol
ABSTRACT: Existing research on Atheists is sparse. The lived experiences of Atheists have been ignored almost entirely. Triangulating from autoethnographic materials and life-history interviews, this project documents the ways that Atheist individuals understand the stigmas attributed to them and their responses to it. Some of the behaviors are framed as "techniques of information control" such as "compartmentalizing" and "passing." Others are framed as "Identity Politics." Techniques of information control and identity politics may serve to impede efforts toward effective activism on behalf of Atheists. Taken from an alternative perspective, Atheism is deconstructed as a form of "queerness" in relation to religion.